1997
DOI: 10.1103/physrevlett.79.784
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain de Broglie Wave Interferometry

Abstract: We report the development of an atom interferometer that uses optical standing waves as phase gratings and operates in the time domain. The observed signal is entirely caused by the wave nature of the atomic center-of-mass motion. The opportunities to measure recoil frequency and gravity acceleration are demonstrated. [S0031-9007(97) PACS numbers: 03.75. Dg, 06.20.Jr, 32.80.Pj, 42.50.Md Atom optics and interferometry is a field that has undergone considerable development in recent years [1]. Atom interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
176
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(180 citation statements)
references
References 18 publications
(26 reference statements)
2
176
1
1
Order By: Relevance
“…Periodic collapses of the momentum splitting of the diffracted atoms were observed. The general technique of temporal atom optics of supercold BEC atoms used in our experiment is very promising for further studies of other phenomena, such as atomic beam splitters [13] and temporal atom interferometers [14]. This method permits investigation of the limiting resolution of atom lithography in the absence of chromatic aberrations and surface diffusion of deposited atoms [8].…”
Section: Diffraction Of a Released Bose-einstein Condensate By A Pulsmentioning
confidence: 99%
“…Periodic collapses of the momentum splitting of the diffracted atoms were observed. The general technique of temporal atom optics of supercold BEC atoms used in our experiment is very promising for further studies of other phenomena, such as atomic beam splitters [13] and temporal atom interferometers [14]. This method permits investigation of the limiting resolution of atom lithography in the absence of chromatic aberrations and surface diffusion of deposited atoms [8].…”
Section: Diffraction Of a Released Bose-einstein Condensate By A Pulsmentioning
confidence: 99%
“…One could have equally well ionized all the excited state atoms immediately following the pulse. The Fourier components, ρ gg (s, t) , and total density, ρ gg (r, t) = s ρ gg (s, t) e isq·r , are periodic functions having period equal to 2π/ω q and can be used to measure recoil frequency [23,35], but, in contrast to scattering by phase gratings, there is no time for which the density is uniform when ω d t ≫ 1. When all Fourier components are taken into account, and for large pulse areas (but not so large as to violate the Raman-Nath approximation),…”
Section: One Field-interaction Zonementioning
confidence: 99%
“…Atom interferometers can be constructed using two or more field interaction zones [22][23][24]. In the transient echo experiment of Cahn et al [23], the vanishing of spatial modulation at the echo times t = 2T and t = 3T (but not in the immediate vicinity of the echo times) is consistent with MWAI theory [25]. Cahn et al also found that the spatial modulation vanished in the classical scattering region, ω q T ≪ 1, as it must for any MWAI.…”
Section: Introductionmentioning
confidence: 99%
“…Matter wave interferometry has demonstrated orders of magnitude improvement over a wide range of precision measurements [1][2][3][4][5][6][7][8]. These successes have spurred interest in transitioning cold atom devices from the lab to more demanding environments [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%